TINGKAT KEBERHASILAN KEGIATAN REHABILITAS DAERAH ALIRAN SUNGAI (DAS) DI PT BORNEO INDOBARA LOKASI DESA ARTAINKECAMATAN ARANIO KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Yusuf Yuliadi; Yusanto Nugroho; Suyanto Suyanto; Kissinger Kissinger (EnviroScienteae, 2023)
PT Borneo Indobara as the holder of a Borrow-to-Use Forest Area Permit and has obligations as the executor of rehabilitation activities. Forest development activities through rehabilitation, especially on critical land in watershed areas (DAS) are one of the efforts that can be made to reduce the adverse effects of forest degradation. Watershed management is a series of efforts made by humans to rationally utilize watershed natural resources in order to fulfill their daily needs and improve their standard of living. Analyzing the success of the activity by looking at the percentage of growth of watershed rehabilitation plants at PT. Borneo Indobara, Artain Village, Evaluate the implementation of activities in the field with the Technical Design on plant growth factors, Analyze the types of plants with the requirements for plant growth, Make recommendations in the Technical Design activities on plant growth factors. The average yield of growth (height and diameter) of plants in 45 land units was 0.67 in height and 0.625 in diameter, 33 in 0.53 in height and 0.475 in land units, 0.57 in 52 in height and 0.505 in diameter. The percentage of survival on land unit 45 was 65.56%, land unit 33 was 64.17%, land unit 52 was 66.36%. Based on the analysis of plant survival percentage, it shows that the average survival percentage of plants is still below 65%, this means that the selected watershed rehabilitation plants need to be evaluated. sea sengon, mahogany, johar, pioneer species of trembesi which are relatively adapted to thin solums. Plant recommendation models are proposed for reclamation plant improvement starting from technical design, to field application so that reclamation plants can show high plant success.